Man in space: A new dimension in Health Care - L. Medlen (AOSIS, 1983)
Unprecedented advances in technology and science in the 20th Century have enabled man to take himself and his inventions on voyages of space exploration. It has been man's dream for centuries, not only to fly, but also to explore the vast outer reaches of space. Modern space exploration, the new frontier, is a triumph for the new sciences of space biology and space medicine.